2013
DOI: 10.1111/febs.12221
|View full text |Cite
|
Sign up to set email alerts
|

Functional dysregulation of stem cells during aging: a focus on skeletal muscle stem cells

Abstract: Aging of an organism is associated with the functional decline of tissues and organs, as well as a sharp decline in the regenerative capacity of stem cells. A prevailing view holds that the aging rate of an individual depends on the ratio of tissue attrition to tissue regeneration. Therefore, manipulations that favor the balance towards regeneration may prevent or delay aging. Skeletal muscle is a specialized tissue composed of postmitotic myofibers that contract to generate force. Satellite cells are the adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 125 publications
5
100
1
2
Order By: Relevance
“…The ability of satellite cells to repair injured muscle markedly declines with aging (Cheung & Rando, 2013). Aside from reduced numbers of satellite cells (Garcia‐Prat, Sousa‐Victor, & Munoz‐Canoves, 2013; Shefer, Mark, Richardson, & Yablonka‐Reuveni, 2006), the differentiation capacity of satellite cells is also reduced with aging. Moreover, the number of differentiating satellite cells is decreased in aged mice, as shown by downregulation of differentiation markers such as desmin and myogenin (Charge, Brack, & Hughes, 2002; Collins, Zammit, Ruiz, Morgan, & Partridge, 2007).…”
Section: Introduction Results Discussionmentioning
confidence: 99%
“…The ability of satellite cells to repair injured muscle markedly declines with aging (Cheung & Rando, 2013). Aside from reduced numbers of satellite cells (Garcia‐Prat, Sousa‐Victor, & Munoz‐Canoves, 2013; Shefer, Mark, Richardson, & Yablonka‐Reuveni, 2006), the differentiation capacity of satellite cells is also reduced with aging. Moreover, the number of differentiating satellite cells is decreased in aged mice, as shown by downregulation of differentiation markers such as desmin and myogenin (Charge, Brack, & Hughes, 2002; Collins, Zammit, Ruiz, Morgan, & Partridge, 2007).…”
Section: Introduction Results Discussionmentioning
confidence: 99%
“…109 Moreover, autophagy also has a role in stem cells maintenance, 110 suggesting that this pathway may also fight accelerated aging by maintaining the health of the stem cell population, avoiding loss of regenerative potential. 111 Accumulation of oxidatively generated damage has been implicated in several neurodegenerative diseases such as Parkinson's and Alzheimer's diseases. 112,113 Data point to autophagy as an important factor in the context of both the pathogenesis and, consequently, therapy of these pathologies.…”
Section: Parpmentioning
confidence: 99%
“…During sarcopenia, loss of skeletal muscle mass is caused by both a loss of myofibers and a decrease in myofiber cross-sectional area 20,21) . Because myonuclei are post-mitotic, and only satellite cells are added to myofibers and contribute myonuclei, it was hypothesized that a decline in satellite cell replenishment of myonuclei contributed to sarcopenia 22,23) . In fact, a recent study clearly showed that the number of satellite cells decreases with age, and muscle regeneration is insufficient in aged mice 24) .…”
Section: Contribution Of Satellite Cells To Muscle Maintenance Duringmentioning
confidence: 99%